USING OF FOREIGN EXPERIENCE OF IMPLEMENTATION MONETARY POLICY IN KAZAKHSTAN - G. T. Kaliyeva,; K. B. Kashkimbayeva, (Academic Journal of Physical and Chemical Sciences, 2019)
The paper is of particular interest to consider the features of the functioning of the banking system in Japan, the United States and the United Kingdom and their experience in implementing monetary policy. Economically leading countries, such as the United States, Japan and the United Kingdom, are less and less using direct directive regulation of the economy, preferring market methods, which gave a tremendous impetus to the development of financial infrastructure. The paper presents a reasonable need to revise the methods for developing and implementing monetary policy in the country for four reasons. First, the lessons of the ongoing global financial crisis make it necessary to adjust the country's monetary policy. Secondly, the main trends in the development of the world economy require changes in the national economy, which require a review of the policies of central banks. Thirdly, chronic deviations from the targets of the money supply force us to take a closer look at how central banks should pursue monetary policy. Fourthly, the monetary policy pursued should be coupled with indicators of the implementation of the state’s industrial and innovative policy, as the world experience in the development and implementation of monetary policy considered in the paper teaches.